(untitled) (Symposium on Natural and Applied Sciences, 2026)
Physical experimentation is a cornerstone of science education, yet the transition from hands-on laboratory work to digital simulation environments raises fundamental pedagogical questions about how students construct understanding through modelling activity. This paper argues that Activity Theory - as developed by Vygotsky, Leontiev, and Davydov within the cultural-historical tradition - provides the most coherent theoretical foundation for the pedagogical design of physical experiment modelling. The paper identifies three activity-theoretic principles that are especially consequential for modelling instruction: the primacy of joint (collective) activity over individual activity in the formation of higher mental functions; the mediating role of signs and symbolic tools in the development of scientific reasoning; and the necessity of reflective activity as the condition for genuine appropriation of modelling skills.